Andrographolide Sulfonate Is a Promising Treatment to Combat Methicillin-resistant Staphylococcus aureus and Its Biofilms - Zhang, Lulu; Wen, Bo; Bao, Mei; Cheng, Yungchi; Mahmood, Tariq; Yang, Weifeng; Chen, Qing; Lv, Lang; Li, Li; Yi, Jianfeng; Xie, Ning; Lu, Cheng; et al. (Frontiers in Pharmacology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is a drug-resistant pathogen threatening human health and safety. Biofilms are an important cause of its drug resistance and pathogenicity. Inhibition and elimination of the biofilms is an important strategy for the treatment of MRSA infection. Andrographolide sulfonate (AS) is an active component of the traditional herbal medicine Andrographis paniculata. This study aims to explore the inhibitory effect and corresponding mechanisms of AS on MRSA and its biofilms. Three doses of AS (6.25, 12.5 and 25 mg/mL) were introduced to MRSA with biofilms. In vitro antibacterial testing and morphological observation were used to confirm the inhibitory effect of AS on MRSA with biofilms. RT-PCR and metabonomics were used to explore the underlying mechanisms of the effect by studying the expression of biofilm-related genes and endogenous metabolites. AS displayed significant anti-MRSA activity and its minimum inhibitory concentration was 50 μg/mL, and AS inhibited biofilms and improved biofilm permeability. The mechanisms are mediated by the inhibition of the expression of genes such as quorum sensing (QS) system regulatory genes (agrD and sarA), microbial surface components recognizing adhesive matrix genes (clfA and fnbB), intercellular adhesion genes (icaA, icaD and PIA) and a gene related to cellular eDNA release (cidA), and the downregulation of five biofilm-related metabolites, including anthranilic acid, D-lactic acid, kynurenine, L-homocitrulline and sebacic acid. This study provided valuable evidence for the activity of AS against MRSA and its biofilm and extended the methods to combat MRSA infection.